(NH4)2[Ni(H2O)6]2V10O28 ⋅ 4H2O; Structural Analysis and Bactericidal Activity against Pathogenic Gram Negative Bacteria. Issue 15 (21st April 2021) - Mahmoud, Ghada Abd‐Elmonsef; Ibrahim, Ahmed B. M.; Mayer, Peter
Abstract: A bis(hexaaquanickel(II)) complex‐decavanadate cluster compound, (NH4 )2 [Ni(H2 O)6 ]2 V10 O28  ⋅ 4H2 O, was synthesized. This compound has been structurally characterized by infrared spectroscopy and single crystal XRD analysis that indicated its triclinic P −1 space group. Additionally, the thermal decomposition mechanism of the compound to a composite of V2 O5 and Ni(VO3 )2 was elucidated. The common antibacterial agents are organics that experience instability and cause pollution to the environment, therefore we wish to consider the synthesis of inorganic bactericides. (NH4 )2 [Ni(H2 O)6 ]2 V10 O28  ⋅ 4H2 O, in comparison to chloramphenicol, led to better inhibition of the growth of five Gram negative human pathogenic bacterial strains ( Escherichia coli, Klebsiella pneumonia, Serratia marcescens, Serratia plymuthica and Pseudomonas aeruginosa) . Remarkably, the highest inhibition was displayed against Escherichia coli that was inhibited completely at (NH4 )2 [Ni(H2 O)6 ]2 V10 O28  ⋅ 4H2 O (50 μg/ml), while the Escherichia coli growth was of 12.93×10 7 ±0.25 CFU/ml at (NH4 )2 [Ni(H2 O)6 ]2 V10 O28  ⋅ 4H2 O (5 μg/ml). This is in contrast to chloramphenicol (5 μg/ml) that allowed for Escherichia coli growth of 13.97×10 7 ±0.24 CFU/ml (control=17.33×10 7 ±0.48 CFU/ml). Abstract : (NH4 )2 [Ni(H2 O)6 ]2 V10 O28  ⋅ 4H2 O, was synthesized. In comparison to chloramphenicol, (NH4 )2 [Ni(H2 O)6 ]2 V10 O28  ⋅ 4H2 O led to better inhibition of the growth of five Gram negative human pathogenic bacterial strains. Remarkably, in contrast to chloramphenicol, the highest inhibition was displayed against Escherichia coli that was inhibited completely at (NH4 )2 [Ni(H2 O)6 ]2 V10 O28  ⋅ 4H2 O (50 μg/ml).